2016
DOI: 10.1007/s11051-016-3597-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonication on particle dispersion, administered dose and metal release of non-functionalized, non-inert metal nanoparticles

Abstract: In this study, we elucidate the effect of different sonication techniques to efficiently prepare particle dispersions from selected non-functionalized NPs (Cu, Al, Mn, ZnO), and corresponding consequences on the particle dose, surface charge and release of metals. Probe sonication was shown to be the preferred method for dispersing non-inert, non-functionalized metal NPs (Cu, Mn, Al). However, rapid sedimentation during sonication resulted in differences between the real and the administered doses in the order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 41 publications
5
112
0
1
Order By: Relevance
“…al. [31] reported that the effect of different sonication techniques to efficiently prepare particle dispersions from selected non-functionalized nanoparticles (Cu, Al, Mn, ZnO), and corresponding consequences on the particle dose, surface charge, and release of metals. W. Li et.…”
Section: F Mehrabi Et Al [29]mentioning
confidence: 99%
“…al. [31] reported that the effect of different sonication techniques to efficiently prepare particle dispersions from selected non-functionalized nanoparticles (Cu, Al, Mn, ZnO), and corresponding consequences on the particle dose, surface charge, and release of metals. W. Li et.…”
Section: F Mehrabi Et Al [29]mentioning
confidence: 99%
“…See more details elsewhere. 22 NPs with concentrations of 1 g L −1 were sonicated for 180 s in ultrapure water in Scint-Burk vials (WHEA986581, Wheaton Industries Inc., USA). The glass vials were positioned in an ice-filled bowl with the sonication probe inserted between the upper quarter and the upper half of the solution in the vial.…”
Section: Nanoparticle Dispersionmentioning
confidence: 99%
“…In addition, three dose tests (triplicates) were prepared from every stock solution directly after sonication in order to determine the actual dose for each exposure, as the real dose can be lower than the nominal dose due to sedimentation. 22 3 × 0.25 mL was pipetted from each stock solution after sonication and digested as described above.…”
Section: Nanoparticle Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 160 ] This sonication approach may not be compatible with some nanocore structures due to the effect of sonication on size and stability of the materials. [ 161 ]…”
Section: Bolstering Cell Membrane Technology With Additional Non‐natimentioning
confidence: 99%